2013
DOI: 10.5114/pjp.2013.38141
|View full text |Cite
|
Sign up to set email alerts
|

Primary mucoepidermoid carcinoma of the breast: a with immunohistochemical analysis and comparison with salivary gland mucoepidermoid carcinomas

Abstract: Mucoepidermoid carcinomas in mammary glands represent 0.3% of all breast tumors. Features of salivary gland mucoepidermoid carcinoma have been used in studies concerning mucoepidermoid carcinomas of the breast because both share similar morphologic and molecular features. We report a case of primary mucoepidermoid carcinoma of the breast with an immunohistochemistry staining panel. We verified that MUC5AC occurs in more than 50% of high-grade tumors, and MUC1 correlates with shorter disease-free survival. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Patients with low-grade MEC were disease free in the follow-up period, whereas high-grade MECs usually showed aggressive behavior with metastasis to axillary nodes and distant organs [17]. Immunohistochemically, MUC5AC is expressed in more than 50% of high-grade tumors and MUC1 expression correlates with shorter disease-free survival [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Patients with low-grade MEC were disease free in the follow-up period, whereas high-grade MECs usually showed aggressive behavior with metastasis to axillary nodes and distant organs [17]. Immunohistochemically, MUC5AC is expressed in more than 50% of high-grade tumors and MUC1 expression correlates with shorter disease-free survival [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Histological classification is determined according to the ratio of cystic components, the presence of neural invasion and necrosis, the mitotic ratio, nuclear grade, border/invasive front, lymphovascular, and bone invasion (Table 2). [16,34] Given their significantly overlapping histomorphologic characteristics, the differential diagnosis of MEC broadly includes intraductal papilloma, clear cell hidradenoma, and adenomyoepithelioma.…”
Section: Discussionmentioning
confidence: 99%
“…Sherwell-Cabello et al [14] 2017 86 6.0 NS LG 0/NS NO 3 Alive NS 9 Cheng et al [15] 2017 Fujino et al [16] 2016 71 1.7 NS IG 0/NS NO NS NS NO 14 Palermo et al [17] 2013 80 4.0 NS HG 0/NS NO NS NS NS 15 Turk et al [18] 2013 40 5.5 CH NS 1/24 NO 5 Alive NS 16 Basbug et al [19] 2011 Di Tommaso et al [23] 2004 80 0. hormone-dependent, and endocrine therapy may an option. Nakano et al [36] reported that patients with MAML2 gene rearrangement were better prognosis.…”
Section: Breast Mec In Clinical Treatment and Prognosismentioning
confidence: 99%